Determinan Kualitas Tidur Mahasiswa Kampus A di Universitas Muhammadiyah Prof DR Hamka - Tristianingsih, Julia; Handayani, Sarah (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2021)
Background. Quality sleep is a basic human need, but in college students, sleep will be disrupted due to student duties and changing lifestyles. If the quality of sleep is not fulfilled or a disturbance, it will affect the decrease in a person's quality of life and decrease the health function. Objective to determine the factors related to sleep quality in Campus A students University Muhammadiyah Prof. Dr. Hamka in 2020. Method. This study used a cross-sectional design with a proportional stratified random sampling technique. The study population was students of Campus A UHAMKA with a sample of 117 students. The data used are primary data using a questionnaire. Data analysis used the chi-square test. Results. The results showed that there were 69 people (59%) of respondents who had poor sleep quality. There is a relationship between the use of gadgets (p=0.001), physical activity (p=0.001), and stress (p=0.001) with sleep quality. Meanwhile, there was no relationship between gender (p= 0.313) and sleep quality. Conclusion. The sleep quality of campus A students at the University of Muhammadiyah Prof DR Hamka is related to the use of gadgets, physical activity and stress.